New dynamics in dynamic geometry: Dragging constructed points. (March 2020) - Selaković, Milica; Marinković, Vesna; Janičić, Predrag
Abstract: Dynamic Geometry Software (DGS) is present for more than three decades: it found its way to classrooms worldwide and it is now an irreplaceable component of mathematical education. From the very beginning and still, DGS tools are built around one central scenario: the user chooses several (free) points and, using them, constructs some other points and other geometric objects. Then, the user can move ("drag") a chosen free point and explore how the constructed points and other constructed objects change. In this paper we describe one new DGS scenario: the user can move the constructed points and explore how the free points and the constructed objects change accordingly. This scenario uses a solver for geometry construction problems. We implemented this DGS feature within our prototype tool Touch&Drag, developed for touch-based devices. The presented feature can be implemented in other DGS tools, too.